The Correlation between Computer Use and Visus of SMKN 2 Surakartaâs Informatic Engineering Students - Lowa, Novy Wahyunengsi; ., Retno Widiati; ., Senyum Indrakila (Nexus Kedokteran Klinik, 2015)
Background : Recently, computers have became primary needs of common people, especially among teenagers. It is proven in the results of a recent study that internet users in Indonesia from among children and adolescents are predicted reach to 30 million. Most computer users spend a lot of time for staring at computer, without give their eyes to rest. As a result, there was a repeated stress on the muscles of the eyes then fatigue. It will continue to decline in the function of the eye muscles that have consequence in visual impairment/decreasing in visual acuity. Methods : This study was analytic observational using cross sectional design that held in November 2014. The subjects of this study were 65 students of class X, XI, and XII SMKN 2 Surakarta who taken by purposive sampling technique through interviews. Analysis of the data used Spearman correlation test which treated with Statistical Product and Service Solutions (SPSS) 20.0 for Windows . Results : In this study indicated that there was no significant relationship between the duration of use of computer vision to the decline in students of N 2 Surakarta , where the value of p = 0.800 ( > 0.05) (old and right visual acuity) and p = 0593 ( > 0.05) (old and left visual acuity) .Conclusions : There is no relationship between the duration of use of the computer vision student N 2 Surakarta .Key Words : Computer use duration, visus, students